PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR LUAS BANGUN DATAR SISWA KELAS V SEKOLAH DASAR - harzona, willya anggraini; Zainil, Melva; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The purpose of this research is to knowing the effect of the Contextual Teaching and Learning approach on learning outcomes to determine the area of building a trapezoid and the kite of class V students of SDN 38 Lubuk Buaya in the 2018/2019 academic year. This type of research is quasi-experimental. The population in this study were all fifth grade students of Gugus 2 Elementary School in Koto Tangah District consisting of 250 students. The sampling technique uses probability sampling and cluster random sampling technique by determining which area will be used as a sample with random to determine the experimental and control classes so that the VA class is obtained as the control group and the VB class is the experimental group. Data collection techniques in this study use tests, test hypotheses in this study using the t-test formula which is preceded by an analysis prerequisite test using normality test and homogeneity test. The results showed that there was a positive and significant influence on the Contextual Teaching and Learning approach to learning outcomes to determine the area of trapezoid and kite of class V students of SDN 38 Lubuk Buaya. This is evidenced by the results of the t-test with a significant level of 5% (0.05) obtained by tcount (4.10)> t table (1.67). Learning outcomes obtained by the experimental group were higher than the control group, indicated by the posttest mean obtained by the experimental group 87.25 and the posttest mean obtained by the control group by 75.3. Keywords: Contextual Teaching and Learning approach, determining the area of trapezoid and kite.